Effects of Ultraviolet Light Treatment in Ambient Air on Lithium-Ion Battery Graphite and PVDF Binder. Issue 6 (1st January 2019) - An, Seong Jin; Li, Jianlin; Daniel, Claus; Wood, David L.
Abstract : In our prior study, ultraviolet (UV) light was used for the first time to improve long-term cycling of lithium-ion battery (LIB) electrodes. It was found that UV treatment of the anode resulted in thinner solid electrolyte interphase (SEI) layers, higher capacity retentions, and lower charge transfer resistance after cycling. In this study, pristine graphite powders and polyvinylidene fluoride films (binder) with/without UV treatment were individually analyzed before cell assemblies. X-ray photoelectron spectroscopy (XPS) analysis showed a 300% increase in atomic percentage of oxygen on the graphite powder surfaces after UV treatment. However, fluorine level of the binder film decreased by more than 10%. The PVDF film also expanded in thickness by 3.7% after the UV treatment for 40 minutes, indicating scissions of the polymer backbones. The changes in PVDF weight, thickness, and fluorine atomic percentage from XPS peaks also indicated the release of fluorine containing gases (e.g., hydrogen fluoride and difluoroethylene gas) after crosslinking and scission of the PVDF. Although UV light was found to partially decompose PVDF in this study, it helped to increase oxygen level on the graphite, which, resulted in a thinner SEI layer, lower resistance, and eventually higher capacity retention as shown in our prior study.